Anthropometric and physical fitness characterization of male elite karate athletes - Sánchez-Puccini, M. B.; Argothy-Bucheli, R. E.; Meneses-Echavez, J. F.; López-Albán, C. A.; Ramirez-Vélez, R. (International Journal of Morphology, 2014)
This study aimed to assess anthropometric and physical fitness characteristics of male elite karate athletes. Our study was carried out on a sample of 19 male Karate Athletes from Colombia (mean age 31.6±8.8 years). Different anthropometric measurements were taken (weight, height, diameters, circumferences, body composition) from which several anthropometric indices were calculated (body mass index, ponderal index, body index adiposity), and the somatotype was then determined. The performance tests carried out were: Astrand-Ryming protocol, vertical jump, anaerobic power and Wingate anaerobic test. The results (mean±SD) showed a body mass (65.4±12.0 kg), height (167.4±9.3 cm), percent body fat (13.6±3.0 %), ponderal index (41.0±1.8) and body adiposity index (25.1±3.6). The somatotype component values according to the Heath-Carter method were (4.0-4.2-2.1) for the endomorphic, mesomorphic, and ectomorphic components respectively. The aerobic capacity average was (44.8±7.1 ml·kg-1·min-1), vertical jump (32.0±8.7 cm) anaerobic power (90.1±22.7 kg·s-1) and anaerobic capacity (5748.7±1477.5 W). These results may provide a profile of elite karate that can be used as training targets for developing athletes. Our findings provide novel insight for both tactical and functional training.